Population-based study of ischemic stroke risk after trauma in children and young adults. (5th December 2017) - Fox, Christine K.; Hills, Nancy K.; Vinson, David R.; Numis, Adam L.; Dicker, Rochelle A.; Sidney, Stephen; Fullerton, Heather J.
Abstract : Objective: To quantify the incidence, timing, and risk of ischemic stroke after trauma in a population-based young cohort. Methods: We electronically identified trauma patients (<50 years old) from a population enrolled in a Northern Californian integrated health care delivery system (1997–2011). Within this cohort, we identified cases of arterial ischemic stroke within 4 weeks of trauma and 3 controls per case. A physician panel reviewed medical records, confirmed cases, and adjudicated whether the stroke was related to trauma. We calculated the 4-week stroke incidence and estimated stroke odds ratios (OR) by injury location using logistic regression. Results: From 1, 308, 009 trauma encounters, we confirmed 52 trauma-related ischemic strokes. The 4-week stroke incidence was 4.0 per 100, 000 encounters (95% confidence interval [CI] 3.0–5.2). Trauma was multisystem in 26 (50%). In 19 (37%), the stroke occurred on the day of trauma, and all occurred within 15 days. In 7/28 cases with cerebrovascular angiography at the time of trauma, no abnormalities were detected. In unadjusted analyses, head, neck, chest, back, and abdominal injuries increased stroke risk. Only head (OR 4.1, CI 1.1–14.9) and neck (OR 5.6, CI 1.03–30.9) injuries remained associated with stroke after adjusting for demographics and trauma severity markers (multisystem trauma, motor vehicle collision, arrival by ambulance, intubation). Conclusions: Stroke risk is elevated for 2 weeks after trauma. Onset is frequently delayed, providing an opportunity for stroke prevention during this period. However, in one-quarter of stroke cases with cerebrovascular angiography at the time of trauma, no vascular abnormality was detected.